Increased crop diversity reduces the functional space available for weeds. (25th November 2019) - Pakeman, R J; Brooker, R W; Karley, A J; Newton, A C; Mitchell, C; Hewison, R L; Pollenus, J; Guy, D C; Schöb, C
Summary: There is a drive to improve the sustainability of agricultural systems including the biodiversity component. Cultivar mixtures offer yield benefits from the same land area, but the mechanisms behind this overyielding have not been completely worked out. One potential mechanism is improved competition with weeds. We use an experimental approach of varying barley ( Hordeum vulgare L.) genotypic and phenotypic diversity to test the hypothesis that increases in diversity have an impact on weed growth strategies and community assembly, or if responses are driven by barley performance. There was no effect of increasing barley mixture diversity on weed traits, either in terms of species means or the community‐weighted mean. However, Functional Richness of the weed community decreased with increasing barley mixture diversity mainly as a result of reduced specific leaf area Functional Richness. This pattern was driven by a reduction in species richness of the weed community rather than by reduced variation within species. Whilst barley phenotype had different impacts on weed traits, there were no specific mixtures of phenotypes or genotypes that had consistent effects on community assembly or weed species responses. The competitive exclusion of weed species could have agronomic and environmental benefits, through better targeting or less frequent use of herbicides. Growing crop mixtures is one of many strategies available to improve agricultural sustainability and resilience, and one that has clear benefits.